“Tratamientos in vitro con fitofármacos contra microorganismos aislados de abscesos cutáneos en ovinos criollos”. - Candelario Gutiérrez, José Eduardo (2020)
The trial was developed with a completely randomized design with bifactorial arrangement, as factor A were found the antimicrobials (anamu, garlic, ginger and neem and 4 antibiotics), as factor B the concentrations (25, 50, 75 and 100%), with five controls that were analyzed by contrasts, forming 32 treatments and 2 repetitions. For the comparison of means between treatments, Tukey's test was used (p≤ 0.05). According to the analysis of variance, the interaction of factors A (antimicrobial) x B (concentrations), showed highly significant differences (p≤0,05), with a variability coefficient of 2.32%, being the best treatment T16 (antibiotic 4 at 100%) with a value of 28.50, this because, the larger the halo diameter, the greater the inhibition of bacteria. It was followed by T15, T12, T4 and T13 with values of 26.50, 25.50, 25.00 and 20.50 respectively, causing in all these cases sensitivity to bacterial populations. Otherwise, it occurred with T9, T10, T17, T18, T19, T20, T21, T22, T23, T24, T25, T26, T27, T28, T29, T30, T31 and T32 with inhibition halos of 0.00 mm, which would indicate that its inhibiting effect was null. This allowed demonstrating at present that despite the potential that these medicinal plants have shown in this study, it was not possible to confirm that potential, since the bacterial agents that cause abscesses in sheep were resistant, in concentrations of 25, 50, 75 and 100%. They were largely overcome by treatments that included the use of antibiotics. Keywords: Abscesses, ethnoveterinary, phytocomponents, sheep, medicinal plants